Addressing Challenges of Surveying Practical Fieldwork Training During COVID-19 Restrictions - El-Mowafy, Ahmed (2021)
Education in Surveying combines learning theoretical concepts and fieldwork training. A major challenge during the COVID-19 restrictions is the ban of fieldwork. This presentation discusses the approaches developed in the Surveying program at Curtin University to enable Surveying students gain fieldwork experience close to what they get from actual fieldwork to continue with their program. Blended learning methods were at the core. Video technology was used for development of practical skills by providing authentic-like recordings for demonstration of equipment usage and practical procedures. Complete fieldwork exercises were set using data collected from previous years. Interactive Simulation-based virtual e-learning tools were developed that are accessible via learning management systems, such as Blackboard, to mimic the implementation of fieldwork tasks. In a virtual environment setting, these tools were designed to allow students to engage and experiment through practicing data entry, fieldwork calculations and checking, and reflect on their practice. The feedback is immediate as it is applied within each task itself. Moreover, in live scheduled online sessions, students communicate with each other and with tutors to receive their guidance and feedback so as to successfully complete the exercises and present results in a format suitable for potential clients. The response from students about the e-learning tools, design of activities and assessments is that they found them useful in developing their understanding and ability to carry out fieldwork, leading to a high student satisfaction of 90%. The developed tools will be utilised for a more engaging education after the COVID-19 period.